2009
DOI: 10.1186/1476-8518-7-4
|View full text |Cite
|
Sign up to set email alerts
|

DNA vaccine containing the mycobacterial hsp65 gene prevented insulitis in MLD-STZ diabetes

Abstract: Background: Our group previously demonstrated that a DNA plasmid encoding the mycobacterial 65-kDa heat shock protein (DNA-HSP65) displayed prophylactic and therapeutic effect in a mice model for tuberculosis. This protection was attributed to induction of a strong cellular immunity against HSP65. As specific immunity to HSP60 family has been detected in arthritis, multiple sclerosis and diabetes, the vaccination procedure with DNA-HSP65 could induce a cross-reactive immune response that could trigger or worse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Previous studies have revealed that the preponderance of the Th2-type cytokines IL-4 and IL-10 prevented the destruction of β cells (Müller, Schott-Ohly, Dohle, & Gleichmann, 2002;Santos et al, 2009). Increases in the production of IL-10 are generally considered an antiinflammatory cytokine that acts mostly on antigen-presenting cells by inhibiting antigen presentation and the production of inflammatory cytokines.…”
Section: Fig 5 -Effect Of the Selected Strains On Faecal Microbiota mentioning
confidence: 98%
“…Previous studies have revealed that the preponderance of the Th2-type cytokines IL-4 and IL-10 prevented the destruction of β cells (Müller, Schott-Ohly, Dohle, & Gleichmann, 2002;Santos et al, 2009). Increases in the production of IL-10 are generally considered an antiinflammatory cytokine that acts mostly on antigen-presenting cells by inhibiting antigen presentation and the production of inflammatory cytokines.…”
Section: Fig 5 -Effect Of the Selected Strains On Faecal Microbiota mentioning
confidence: 98%
“…within 15 min. of preparation) for five consecutive days [19]. The mice were monitored for fasting glucose levels in blood samples (obtained from the tail vein of mice after 6 h of fasting) once in a week starting from 7 days after the last dose of STZ.…”
Section: Experimental Animalsmentioning
confidence: 99%
“…The result was expressed as the percentage of islet area showing mononuclear cell infiltration, according to the formula: mononuclear infiltrate area (m 2 ) × 100/islet area (m 2 ). Finally, the results were categorized into the following score: 0 = intact islet; 1 = peri-insulitis (≤10% of the islet infiltrated); 2 = moderate insulitis (≤50% of the islet infiltrated); 3 = severe insulitis (≥50% of the islet infiltrated); and 4 = destructive insulitis (Santos et al, 2009). At least 20 islets per pancreas were analyzed in non-consecutive sections.…”
Section: Morphometric Analysis Of Pancreatic Insulitismentioning
confidence: 99%
“…Peripheral changes such as downregulation of Th2-derived cytokines and inhibition of Treg cells were also demonstrated (Zdravkovic et al, 2009). One of the advantages of this model is the fact that hyperglycemia and insulitis are observed in a relatively short period of time (2-3 weeks after the last STZ injection) in a high percentage of animals (Paik et al, 1980;Santos et al, 2009).…”
Section: Introductionmentioning
confidence: 95%